Seroprevalence and associated risk factors of leptospirosis in slaughter pigs: A neglected public health risk, western Kenya - Ngugi, J.N.; Fèvre, Eric M.; Mgode, G.F.; Obonyo, M.; Mhamphi, G.G.; Otieno, C.A.; Cook, Elizabeth A.J. (Springer, 2019)
Background Leptospirosis is a neglected zoonosis of public health importance transmitted through contact with contaminated soil, water or urine of infected animals. In pigs the disease is characterized by abortion, still births and weak piglets. A cross-sectional study was conducted in May to July 2018 to estimate the sero-prevalence of leptospirosis and factors associated with seropositivity in slaughter pigs. A questionnaire was used to collect information on animal demographics. Serum was tested for anti-leptospiral antibodies using microscopic agglutination test (MAT) with a panel of 8 serovars. Sera were considered positive for sero-reactivity at a MAT titre ≥1:40 against at least one serovar. Chi-square tests were used to measure the strength of association between the MAT test result and exploratory variables. Results A total of 252 pig serum samples from seven slaughterhouses were tested for Leptospira antibodies by MAT. Of the 252 pigs sampled, 88.8% (244/252) were indigenous breeds; 55.6% (140/252) were female and 88.7% (220/252) were reared in extensive production systems. Eighty-three (32.9%; 83/252) sera samples tested positive on MAT against at least one serovar. Of the 8 serovars, the highest prevalence was recorded for serovar Lora 21.4% followed by Kenya 5.2%, Sokoine 3.6% and Grippotyphosa at 3.2%. Risk factors for leptospirosis seropositivity in pigs were: originating from farms with other types of livestock (OR 2.3; 95% CI 1.0–4.5) and mature pigs (OR 1.9; 95% CI 1.1–3.3). Conclusion This study demonstrates that there is a high prevalence of leptospirosis positive pigs at slaughter in a small-holder livestock keeping region of the Lake Victoria basin. The potential for cross species transmission of pathogenic serovars is highlighted as well as the potential for occupational exposure to slaughterhouse personnel. Improvements in husbandry practices (confinement and rodent control) and public health education among slaughterhouse workers and other high-risk groups is recommended.